2019
DOI: 10.1177/0021998319853033
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experiment on the effect of patch shape on adhesive repair of composite structures

Abstract: In order to investigate the performance of the adhesive bonding repair in composite structures, static tensile test is carried out on the bonding structures numerically and experimentally. The tensile stress–displacement behaviors of T7901 composite adhesive bonding structure is studied under room temperature. Based on the three-dimensional progressive damage theory, the model of adhesive bonding structures with different patch shape has been constructed, and the final failure strength is predicted using APDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It is generally expected that the shape of the repair patch as well as its thickness have an effect on strength recovery. 31 For instance, thicker patches will lead to higher failure loads. 32,33
Figure 13.Strength of open-hole and repaired samples from configuration shown in Figure 5 for UD, PW, and TW laminates.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally expected that the shape of the repair patch as well as its thickness have an effect on strength recovery. 31 For instance, thicker patches will lead to higher failure loads. 32,33
Figure 13.Strength of open-hole and repaired samples from configuration shown in Figure 5 for UD, PW, and TW laminates.
…”
Section: Resultsmentioning
confidence: 99%
“…It is generally expected that the shape of the repair patch as well as its thickness have an effect on strength recovery. 31 For instance, thicker patches will lead to higher failure loads. 32,33 Upon investigating the failure surfaces for repaired samples, similar failure modes were generally observed for both repair methods, explaining the similar strength values presented in Figure 13.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…For thin sheets, the one-sided patch is useful but for thicker plates, it has less effect. 33 In Li et al., 34 the effect of patch shape on the repair efficiency was investigated, and it was observed that the square patch has a better performance than other patches. In Mhamdia et al., 35 by examining the effect of the patch shape on the repair performance in aerospace structures, it was concluded that the rectangular shape performance can be improved by using H-shape and the H-shape performance will be improved by the arrow shape (Figure 5).…”
Section: The Effect Of the Patch Adhesive And Main Plate Geometry Onmentioning
confidence: 99%
“…The effect of intralaminar damage can be taken into account by reducing the stiffness coefficients. Here, we adopt the model shown in equation (13) to compute the degradation of coefficients of the stiffness matrix. The relation between the effective stressp and the nominal stress isp…”
Section: Cohesive Zone Model For the Interlaminar And Bonding Interfamentioning
confidence: 99%
“…[10][11][12] The tensile stress-displacement behaviors of T7901 composite adhesive bonding structure was studied under room temperature. 13 Vaidya et al 14 found that the out-of-plane load causes higher peel stress concentration than in-plane load, and adhesive crack mode is the first mixture mode that then transforms into pure mode II. Hence, out-of-plane load (three-point bending (3pb) and fourpoint bending (4pb)) is worth to be studied deeply and systematically.…”
Section: Introductionmentioning
confidence: 99%